2014
DOI: 10.1111/iej.12344
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of an immature tooth with apical periodontitis using a single visit protocol: a case report

Abstract: Disinfection with 5% sodium hypochlorite followed by the induction of a blood clot into the root canal space may be sufficient to promote revascularization in certain circumstances. A single visit revascularization procedure is a potential treatment option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 49 publications
(141 reference statements)
2
82
0
2
Order By: Relevance
“…Previous studies have also suggested limited residual antibacterial properties of NaOCl (29,34). Few endodontic regeneration case reports have demonstrated successful root canal disinfection using irrigation solutions without supplementary inter-appointment medicaments (5,6). However, the use of antibiotic intra-canal medicaments such as TAP in addition to irrigation solutions can be extremely helpful when an extended residual antibacterial effect is required (10).…”
Section: A3mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also suggested limited residual antibacterial properties of NaOCl (29,34). Few endodontic regeneration case reports have demonstrated successful root canal disinfection using irrigation solutions without supplementary inter-appointment medicaments (5,6). However, the use of antibiotic intra-canal medicaments such as TAP in addition to irrigation solutions can be extremely helpful when an extended residual antibacterial effect is required (10).…”
Section: A3mentioning
confidence: 99%
“…Numerous studies have reported the success of this technique with regard to resolution of infection and continuous development of the immature roots (3,4). Root canal disinfection is imperative for successful endodontic regeneration procedures, and various antimicrobials have been used for this, including irrigation solutions such as sodium hypochlorite (NaOCl) (5) and chlorohexidine (6), inter-appointment medicaments such as calcium hydroxide (7), or various antibiotic mixtures (3). A recent systemic review found that 80% of clinical endodontic regeneration studies and case reports used antibiotic combinations as intracanal medicaments (8).…”
Section: Introductionmentioning
confidence: 99%
“…Because of it excellent sealing properties and biocompatibility, mineral trioxide aggregate (MTA) has been the material of choice for covering the blood clot [6,9,17,18]. However, placing MTA over a soft blood clot can be a formidible task; MTA may collapse into the newly-formed clot during condensation [19].…”
Section: Introductionmentioning
confidence: 99%
“…MTA needs to be placed at the level of the cervical constriction or even a little more coronally (27). A more coronal placement of MTA will potentially achieve hard tissue formation in the critical cervical area of the tooth which is where catastrophic fractures appear to occur (28).…”
mentioning
confidence: 99%